2020
DOI: 10.1002/ange.202011778
|View full text |Cite
|
Sign up to set email alerts
|

CoNi Alloy Nanoparticles Embedded in Metal–Organic Framework‐Derived Carbon for the Highly Efficient Separation of Xenon and Krypton via a Charge‐Transfer Effect

Abstract: Separation of Xe and Kr is one of the greatest challenges in the gas industries owing to their close molecular structure and similar properties. Energy‐effective adsorption‐based separation using chemically stable carbon adsorbents is a promising technology. We propose a strategy for Xe/Kr separation using MOF‐derived metallic carbon adsorbents. M‐Gallate (M=Ni, Co) were used as precursors to fabricate CoNi alloy nanoparticles embedded carbon adsorbents by one‐step auto‐reduction pyrolysis. The optimal NiCo@C‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Over the past decades, energy-efficient adsorption separation that has showed great potential in desulfurization encourages the development of task-specific adsorbents. Traditional adsorbents like porous carbons and zeolites have been extensively investigated in SO 2 capture and removal. Nevertheless, porous carbons feature the wide pore size distribution and lack strong binding sites, thus showing low selectivity of SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, energy-efficient adsorption separation that has showed great potential in desulfurization encourages the development of task-specific adsorbents. Traditional adsorbents like porous carbons and zeolites have been extensively investigated in SO 2 capture and removal. Nevertheless, porous carbons feature the wide pore size distribution and lack strong binding sites, thus showing low selectivity of SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…25,42 DFT calculations showed that Ni atoms strongly adsorb onto xenon atoms. 43 To further investigate the effect of the calcination temperature of Ni/AC on the valence state of nickel metal, XPS was adopted to analyze the surface valence of nickel. The chemical states of nickel in Ni/AC are shown in Fig.…”
Section: Morphology and Structure Analysismentioning
confidence: 99%
“…24 Density functional theory calculations have revealed that charge transfer from Xe to Ni or CoNi nanoparticles could result in a higher binding energy and thus the excellent affinity toward Xe. 43 The polarizability of the noble gases increases with the increasing atomic number in the periodic table. Since there seems to be a correlation with the size of the noble atoms, this phenomenon suggests that the efficiency should be even higher for radon.…”
Section: Morphology and Structure Analysismentioning
confidence: 99%
See 2 more Smart Citations